2019
DOI: 10.5539/hes.v9n2p10
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Loneliness - Forever connected?

Abstract: Young adults’ use of social media has soared in recent years, and the many hours that young adults now spend in front of screens replace time spent in face-to-face interactions. Previous studies indicate that the unique features of social media offer advantages to adolescents compared with other communications media. Today, the fact that young adults spend a significant part of their social lives spent on social media and forums triggers an important question that interests educators and therapists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
1
24
0
6
Order By: Relevance
“…We just tried to identify the features of the content shared by users experiencing loneliness and to identify some general trend. Today, unfortunately, the question of the relationship of loneliness and the use of social networks remains unresolved, and many authors (Nowland et al, 2018;Ortiz-Ospina & Roser, 2020;Yavich et al, 2019) talk about the inconsistency of research data on this topic. The relationship between experiencing loneliness and using social networks is dynamic and bidirectional.…”
Section: Resultsmentioning
confidence: 99%
“…We just tried to identify the features of the content shared by users experiencing loneliness and to identify some general trend. Today, unfortunately, the question of the relationship of loneliness and the use of social networks remains unresolved, and many authors (Nowland et al, 2018;Ortiz-Ospina & Roser, 2020;Yavich et al, 2019) talk about the inconsistency of research data on this topic. The relationship between experiencing loneliness and using social networks is dynamic and bidirectional.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings add to the debate about the role of social media use in youth loneliness. Several studies report a link between increased social media use and loneliness, 40,41,42 while others report no such association 43 or that results vary based on type of social media platform. 44 Our study found that social media use was not a predictor of youth loneliness, while contrastingly, face to face contact (e.g., going out with friends) was associated with reduced loneliness.…”
Section: What This Study Addsmentioning
confidence: 99%
“…El área de seguridad aparece influenciada por la familia, concienciada sobre los peligros que conlleva el uso de internet -y las redes en concreto-(Bacigalupe y Camara, 2011), como se observa en los casos. La comunicación, con la segunda puntuación más alta, empieza a tener especial importancia en esta edad, ya que la interacción con sus iguales es una motivación fundamental para el uso de las tecnologías (Yavich et al, 2019).…”
Section: Conclusionesunclassified